2021
DOI: 10.1108/ijge-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Are women's entrepreneurial intentions and motivations influenced by financial skills?

Abstract: PurposeThis study aims to determine the contribution of financial skills to entrepreneurial intentions among women involved in university education.Design/methodology/approachClustering and logistic regression analyses were used to infer the determinants and motivators of entrepreneurial intention in a sample of women students at a Spanish online university.FindingsFinancial and numerical skills could play a significant role in boosting entrepreneurial culture, overcoming reticence and increasing awareness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 114 publications
1
2
0
Order By: Relevance
“…(2022) conclude that women with a higher level of financial literacy in the United States are more likely to be self-employed than men. Llados-Masllorens and Ruiz-Dotras (2021) report similar findings and report that financial and numerical skills boost entrepreneurial culture among women. However, the question remains: does digital financial literacy promote financial inclusion for women entrepreneurs?…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 63%
“…(2022) conclude that women with a higher level of financial literacy in the United States are more likely to be self-employed than men. Llados-Masllorens and Ruiz-Dotras (2021) report similar findings and report that financial and numerical skills boost entrepreneurial culture among women. However, the question remains: does digital financial literacy promote financial inclusion for women entrepreneurs?…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 63%
“…In our third contribution, we enrich intentionality models by focusing on the intersection of sector (STEM) and gender, thus integrating contextual situations (Donaldson, 2019; Llados-Masllorens and Ruiz-Dotras, 2022). Research on entrepreneurial intentions has posited that intentions are shaped by personal factors such as perceived abilities as well as cultural and social contexts (Bird, 1988; Shapero and Sokol, 1982).…”
Section: Discussion Limitations and Future Research Directionsmentioning
confidence: 99%
“…gendered career paths) underpinning the decision to engage in technology entrepreneurship and the role of entrepreneurship education in this process. In doing so, we address recent calls to integrate intentionality models in specific contextual situations (Donaldson, 2019; Llados-Masllorens and Ruiz-Dotras, 2022). By focusing on the intersection of sector and gender, our theorizing enriches extant literature, specifically the personal choice-making within the broader cultural and social environment (Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Nguyen, et al [31] have indicated that financial knowledge does have a beneficial impact on a person's intention to start their own business. The number of studies on financial knowledge in a financial environment and individual entrepreneurial intention, however, was minimal (for example, Llados-Masllorens and Ruiz-Dotras [32]). Also, there are virtually no studies that examine the financial backdrop to identify entrepreneurial purposes in the agriculture sector for financial knowledge.…”
Section: Relationship Between Financial Literacy (Financial Knowledge...mentioning
confidence: 99%